2017
DOI: 10.1039/c7ra07467k
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin as a simple but versatile primer in dentin bonding

Abstract: Poor bonding stability remains the "Achilles' heel" of dentin bonding, a simple and effective approach to inhibit the activities of both exogenous collagenases and endogenous MMPs, and prevention of the growth of bacterial biofilm is therefore highly demanded. In the present study, a quercetin/ethanol solution was developed as a multifunctional primer to pretreat the dentin surface during adhesive restoration. The results showed that pretreatment with quercetin/ethanol solutions (0.5 and 1.0 wt%) on the dentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 50 publications
(36 reference statements)
0
31
0
Order By: Relevance
“…Quercetin has a stronger collagen crosslinking effect and is 100 times less cytotoxic than glutaraldehyde. Quercetin also induces dentinogenic differentiation of dental pulp cells, it has an antibacterial effect by inhibiting the metabolic activity of S. mutans [ 29 ], and inhibits the action of dentin MMPs [ 41 ]. These are important properties because quercetin added to dental bonding agents can increase the resistance of collagen fibrils at the hybrid layer, prevent secondary caries, and induce dental hard tissue formation after placing composite restorations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin has a stronger collagen crosslinking effect and is 100 times less cytotoxic than glutaraldehyde. Quercetin also induces dentinogenic differentiation of dental pulp cells, it has an antibacterial effect by inhibiting the metabolic activity of S. mutans [ 29 ], and inhibits the action of dentin MMPs [ 41 ]. These are important properties because quercetin added to dental bonding agents can increase the resistance of collagen fibrils at the hybrid layer, prevent secondary caries, and induce dental hard tissue formation after placing composite restorations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the cytoprotective effects of antioxidants, treatment of the dentin surface with antioxidants such as RES and quercetin has been shown to preserve adhesive microtensile strength [ 12 , 25 , 41 , 47 ]. However, this is the first study on adding RES and BRP to dental adhesives, and it was not possible to compare our results on bond strength with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Four deciduous dentin samples (npg ¼ 1) were xed to aluminum stubs with double-sided adhesive carbon tape (SPI Supplies, United States). A scanning electron microscopy (JEOL, JSM-6610 LV, Japan) was used to obtain images of changes in roughness, 19,20 with the following settings: low vacuum mode at 10 Pa chamber pressure, an electron acceleration voltage of 20 kV detecting backscattered electrons at a magnication of 1000Â.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…studies [8,[23][24][25][27][28][29]] from 2008 to 2018 were included in the meta-analysis ( Figure 1) and another 5 articles [32,[78][79][80][81] were included in the qualitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The general analysis showed no significant difference between the groups studied, with p=0.063 (95% confidence interval: 0.049-1.906 and random effect model, I 2 = 82.25%). The qualitative analysis included 5 studies [32,[78][79][80][81] and the results showed that the use of MMP inhibitors does not affect initial bond strength values. However, the studies that performed a long-term evaluation [32,78,79,81] showed that the bond strength values were higher for the inhibitor-treated groups compared to untreated groups.…”
Section: Meta Analysismentioning
confidence: 99%